MENGEMBANGKAN KEPERCAYAAN DIRI SISWA SMP YPU BANDUNG MELALUI KEGIATAN PUBLIC SPEAKING - Muhammad Fahmi Abdulah; Iin Surtiah; Rahmat Santa; Sunandie Eko Ginanjar (ABISATYA DINAMIKA ISWARA PUBLISHING, 2022)
Self-confidence as a form of self-recognition of the abilities that exist in the individual. Community service activities carried out by the STIA Bagasasi Bandung lecturer team are about developing student confidence through public speaking at SMP YPU Bandung. The results of observations and interviews with the student affairs department of SMP YPU Bandung that students in grades 7, 8 and grade 9 in communication, delivering presentations or speaking in front of classmates still experience speech anxiety and lack of confidence. The community service activity (PKM) aims to provide explanations to students about the ways and techniques of speaking in public and to improve the public speaking skills of students of SMP YPU Bandung City. PKM is carried out through the following stages. PKM activities go through three pase, namely, the preparation pase, the implementation pase and the evaluation pase. The evaluation of the training seen from the results of the pre-test participants' knowledge of public speaking techniques is still not understanding in its delivery. The results of the post test, participants were able to speak in public, with various versions of participants. The presence of notes for subsequent activities in preparation, completeness of the material. The training went well and all participants were enthusiastic about participating in the activity and wanted to try to explain ideas in public